Determinants of the use of tax consultant services by corporate taxpayers - Herry Aprilia Manubulu; Angela Merici Minggu; Mallia Trisonya Sinaweni (Universitas Muhammadiyah Malang, 2026)
Purpose: This study analyzes the determinants influencing the use of tax consultant services among corporate taxpayers in Kupang City, Indonesia, focusing on tax knowledge, perceptions of tax consultants, perceptions of Account Representatives, and tax audits. Methodology/approach: A quantitative survey method was employed using questionnaire data from 35 corporate taxpayers who had utilized tax consultant services, selected through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with SmartPLS 4. Findings: The results indicate that the perception of tax consultants has a positive and significant effect on the use of tax consultant services. In contrast, tax knowledge, perceptions of Account Representatives, and tax audits do not significantly influence corporate taxpayers’ decisions to use such services. Practical and Theoritical contribution/Originality: This study provides empirical evidence on factors influencing the use of tax consultant services in Eastern Indonesia and highlights the importance of strengthening tax consultants’ professionalism and credibility to enhance taxpayer trust and service utilization. Research Limitation: The study is limited by its small sample size and focus on a single city. Future research should involve larger samples and broader geographic coverage.